Efficacy and safety of plant sterols for controlling blood cholesterol (Philippine Journal of Nutrition, 2007)
Cardiovascular disease is a serious concern in the Philippines. While death from cardiovascular disease, expressed as a proportion of all deaths, is relatively low in the Philippines (less than 20% compared with 30-35% or more in countries such as Australia and New Zealand) (Khor et al 2001), there is still an urgent need to address preventive measures. Lifestyle and behavior, including a healthy diet, regular exercise, not smoking, and avoiding chronic stress, play a key role in helping to prevent cardiovascular disease.